Thermosonic micro-interconnections: Interfacial Cu-Al intermetallics compound growth studies based on stress modelling - Sharir, Shariza (2024)
One of the most common wire bonding technology involving copper (Cu) wire interconnections is the thermosonic bonding technique. Still, the volumetric changes of intermetallic compounds (IMCs) formed at the bonding interface of Cu wire on Al bond pads induce voids formation in the Cu-Al IMC layer. This is much apparent especially after an annealing treatment of High Temperature Storage (HTS). Effects of Cu free air ball and bonding temperature with high temperature storage (HTS) treatment on Cu-Al bonding interface are unclear due to varying observations and inconsistencies in the bonding parameters. A quantitative stress analysis via statistical modelling was constructed to study the characteristic and formation of thermosonic Cu wire-Al bond pad system interfacial microstructure evolution. Objectives of this research are; (1) to study the characteristic and formation of Cu-Al IMC interfacial microstructure layer in thermosonic Cu wire-Al bond pad bonding process based on various bonding temperatures, Cu oxidation condition and HTS durations; (2) to study the influence of the Cu-Al IMC formation to the electrical contact resistance of the system. (3) to develop a theoretical model that describe the interfacial stress field of the Cu wire-Al bond pad system in terms of Cu-Al phase evolution. Microstructural characterizations were focused on Cu-Al IMC crystallographic system and compositional classification. Ball bond mechanical strength analysis were carried out to evaluate the bonding parameters with its strength. The bonding temperature was found to affect the thickness of the initial IMC layer formed at the bonding interface. The amount of the initial IMC formation in turn influences the saturation thickness of the IMC after HTS treatment. In the theoretical part, a stress model was proposed by coupling of both thermal misfit and diffusion induced stresses. It was found that the stress developed by interfacial Cu-Al IMC generally increased with the bonding temperature. The influence of forming gas supply was found to be less significant to affect the interfacial stress development, as the oxide layers did not hinder much the interdiffusion of Cu and Al atoms in the Cu-Al IMC formation. This report addressed the research gaps and presented a better understanding of the fundamental of interfacial Cu-Al IMC in thermosonic micro-interconnection. The results of the stress modelling could be a useful failure analysis technique for implementing Cu wire in the industry. In conclusion, the identified key parameters influencing Cu-Al IMC development and mechanical strength are in the following sequence: HTS duration > bonding temperature > forming gas supply as presented in the correlation matrix of various variables.